G-suite digital school for education - Khairunnisa, Khairuddin (2018)
Malaysian education system nowadays have reach a good standard. Ministry of Education has launch several of education plan in order to bring up our education plan in order to bring up our education level as other developed country. As all the school education organization are working on the plan we have to make sure that we are moving parallel with the passage of time. Therefore, it is better for a school organization to apply the technology usage in their school management. In certain school, they are still left behind in technology. As we can see the school organization are lack of suitable facilities for pleasant teaching and learning environment. Next, they are also lack of effective way in delivering important announcement to the school members. Thus, G-Suite Digital School for Education is introduce to help fellow teachers to educate their student in effective way. By using G-Suite Digital School for Education, it does not just involve the teachers but it also involve the parents, students and also other parties who are interested in knowing about the school. The objectives of this project is to develop a digital school model for effective learning and to test the acceptance of the proposed model through case study. Agile methodology has been embedded in the development of the website for a school organization. The development of website as the methodology and prototype of this study consists of six phases, which are planning phase, analysis phase, design phase, implementation phase, testing phase and maintenance phase. After the website has been developed, the school are able to conduct a pleasant teaching and learning environment to the students and teachers beside able to deliver important announcement to the public effectively.